(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
English, once a language confined to its native shores, has become the lingua franca of the modern world, transcending geographical and cultural boundaries. This article explores the phenomenon of English language globalization, examining its historical roots, driving forces, and implications for global communication. It delves into the key factors contributing to the spread of English, such as colonialism, technology, and economic globalization, and discusses both the benefits and challenges associated with its dominance. Through a comprehensive analysis, this article aims to provide insights into the profound impact of English as a global language and its role in shaping our interconnected world.